2013
DOI: 10.1186/ar4359
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rituximab treatment in early primary Sjögren's syndrome: a prospective, multi-center, follow-up study

Abstract: IntroductionPrimary Sjögren’s syndrome (pSS) is an autoimmune disorder affecting exocrine glands; however, a subgroup of pSS patients experience systemic extra-glandular involvement leading to a worsening of disease prognosis. Current therapeutic options are mainly empiric and often translated by other autoimmune diseases. In the last few years growing evidence suggests that B-cell depletion by rituximab (RTX) is effective also in pSS. Patients with early active disease appear to be those who could benefit the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
128
0
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(155 citation statements)
references
References 57 publications
8
128
0
19
Order By: Relevance
“…Plasma cells are not directly depleted by rituximab, because expression of CD20 is downregulated when B cells differentiate towards plasma cells, but formation of new plasma cells may be impaired by B cell depletion therapy. Although initial studies in pSS showed improvement of both subjective and objective parameters [4][5][6][7], two large placebo-controlled trials [8,9] did not confirm all promising results of the earlier studies. Possible explanations for this discrepancy are heterogeneity in patient characteristics, primary end points and background medication use, which will all be discussed in this review.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Plasma cells are not directly depleted by rituximab, because expression of CD20 is downregulated when B cells differentiate towards plasma cells, but formation of new plasma cells may be impaired by B cell depletion therapy. Although initial studies in pSS showed improvement of both subjective and objective parameters [4][5][6][7], two large placebo-controlled trials [8,9] did not confirm all promising results of the earlier studies. Possible explanations for this discrepancy are heterogeneity in patient characteristics, primary end points and background medication use, which will all be discussed in this review.…”
Section: Introductionmentioning
confidence: 83%
“…While three studies did not find significant changes in anti-SS-A/Ro or anti-SS-B/La autoantibodies after treatment [7,15,16], we found a significant reduction of ±25% in anti-SS-A/Ro and anti-SS-B/La titers at 16 weeks after treatment (Table 1) [17]. The discrepancy between studies may be explained by differences in study population size, baseline systemic disease activity, time point of measurements, or differences in reliability of the immunoassay, but methods for anti-SS-A/Ro and anti-SS-B/La measurement were not specified in most studies.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations